Analysis of galloping response in ice-coated transmission conductors under wind loads - Shuang Wu; Haiqing Liu; Yunlong Wang; Yuxin Wang (PLoS ONE, 2025)
Conductor galloping is a low-frequency, large-amplitude vibration phenomenon induced by the combined action of ice accretion and wind loads, which poses severe threats to power grid safety. For 500 kV transmission lines in Xinjiang, a strain-displacement relationship based on elastic catenary theory was developed, establishing a nonlinear dynamic model for galloping of ice-coated bundled conductors with torsional stiffness. Employing D-shaped, fan-shaped, and crescent-shaped ice-accreted bundle conductors, this work investigates the influence of wake effects and wind attack angles on aerodynamic characteristics at varying spanwise lengths. Subsequently, aerodynamic loads were computed based on the derived aerodynamic coefficients, enabling galloping response analysis of ice-accreted bundle conductors. The results demonstrate that the proposed methodology facilitates efficient analysis of galloping amplitude in ice-accreted transmission conductors, and the three-dimensional numerical model significantly improves the computational accuracy of aerodynamic forces on bundle conductors. The flow field around ice-coated bundled conductors exhibits pronounced periodicity, governed collectively by wake effects, wind attack angle, ice accretion geometry, ice thickness, and wind velocity. Additionally, spacer bars with articulated connections suppress conductor galloping more effectively.